Evaluasi Kurikulum Dan Pembelajaran PAI Dalam Meningkatkan Kualitas Pendidikan Dasar Di Era Digital - Rangga Bagaskara, Figo; Agus Pahrudin; Agus Jatmiko; Koderi (BADA'A: Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research is to determine the effectiveness of the Islamic Religious Education (PAI) curriculum and teaching in improving the quality of basic education in the digital era. To achieve this goal, the research employs a descriptive qualitative methodology using techniques such as classroom observations, in-depth interviews, and document analysis. The research shows that the PAI curriculum combined with digital technology can enhance student engagement in learning, demonstrate the relevance of the material to everyday life, and improve students' understanding of Islamic values. However, primarily due to the lack of training and supporting facilities, some teachers still face difficulties in implementing technology-based methods. This study found that curriculum evaluation must be conducted continuously to ensure its relevance to the demands of the digital era. In addition, the development of digital infrastructure and teacher training are important components in enhancing the effectiveness of PAI learning. This study provides practical recommendations to improve the quality of basic education through curriculum updates that are responsive to technological advancements and student needs.